Comparative analysis of the environmental impacts of port activities in Pernambuco ports | Análise comparativa dos impactos ambientais das atividades portuárias nos portos de Pernambuco - Bezerra, Ana Paula Xavier de Gondra; Santos, Ítala Gabriela Sobral dos; Silva, Maria Carolina da; Gabriel, Fabrício Ângelo; Holanda, Romildo Morant de; Moares, Alex Souza (Revista Geama, 2016)
Port activities can create serious consequences to human health, coastal ecosystems and socioeconomic activities. The panorama of the port sector shows a scenario of intense transformation, whose environmental impacts should be analyzed carefully. The main impacts are due to the port operation and infrastructure deployment activities to promote the transit of cargo. In this sense, the objective of this work is to identify the main environmental impacts from port activities in the state of Pernambuco (Suape and Recife’s). Through this, the proposed methodology was based on conducting research and synthesis from bibliographic material of the area to generate this literature review. It was found that port implementation activities can cause the following impacts: the hydrological pattern and sediment dynamics of natural coastal areas (habitats, ecosystems, changes in the coastline), vegetation removal, modification in the layout and channel changes at the bottom of water bodies, water pollution, soil, subsoil and air. On the other hand, port operation activities can generate environmental problems, such as changes in water quality, air pollution due to the emission of gaseous and solid particles, various disorders due to the traffic of heavy vehicles in the urban environments, generation of odors, noise, change of landscape, disturbances in fauna and flora, the increase of endemic disease vectors in man, and the introduction of exotic species. All these problems have been identified both in Port of Suape and Port of Recife as based on previous survey studies. It is concluded that these activities are necessary for the operation of ports, and in this sense the monitoring of these areas becomes necessary to monitor the risks and environmental impacts so that the actions of the ports do not compromise the ecological balance.